水通道蛋白(aqp1a)在斑馬魚胚胎表皮參與二氧化碳的運送 - 趙珮伶; Pei-lin Chao (2019)
水通道蛋白(aquaporins, AQPs)是一群執行水分子通透的細胞膜蛋白。此外，有些AQPs也被發現具有二氧化碳、甘油、氨與尿素的通透性。因此AQPs 依其功能又區分成三亞群，分別為aquaporins, aquaammoniaporins, 與 aquaglyceroporins三群。在哺乳類研究發現，AQP1缺失的紅血球會降低二氧化碳通透性。最近研究將斑馬魚(Danio rerio) aqp1a表現於蛙卵會增加細胞膜對二氧化碳通透性。然而，目前仍沒有活體的實驗證實AQPs在動物體內參與二氧化碳(carbon dioxide, CO2)通透。本研究利用斑馬魚仔魚為模式動物，探討aqp1a在仔魚表皮細胞上的分佈與功能。將1 % CO2馴養一週的仔魚以real-time PCR分析，結果顯示aqp1a mRNA表現量增加。利用原位雜交與抗體染色標定，發現aqp1a大量表現於卵黃囊表皮上的H+-pump-rich cell與Na+ -pump-rich cell，其他表皮細胞則有少量的表現。利用morpholino knockdown弱化aqp1a蛋白的表現再利用離子選擇電極技術(SIET)分析碳酸排放，發現aqp1a基因弱化的仔魚碳酸的排放減少，顯示aqp1a在胚胎體表細胞扮演CO2通透的功能。 Aquaporins (AQPs, water channels) are integral membrane proteins that facilitate water transport across cell membrane. However, some member of AQPs was also found to facilitate transport of carbon dioxide (CO2), glycerol, ammonia, and urea. According to their properties, AQPs were divided into three functional groups: aquaporins, aquaammoniaporins, and aquaglyceroporins. In mammalian studies, AQP1-deficient erythrocytes were found to decrease permeability to CO2. In vitro studies by expressing mammalian AQP1 or zebrafish aqp1a in Xenopus oocytes showed that AQP1 is able to facilitate CO2 diffusion. However, in vivo study is still lacking to demonstrate AQP1 is involved in CO2 transport in mammals or other vertebrates. In this study, we used zebrafish larvae as an in vivo model to investigate the function of aqp1a. Results showed that aqp1a mRNA in larvae was induced by hypercapnia (1% CO2) treatment for 7 days. In situ hybridization of aqp1a showed that it was highly expressed in H+-pump-rich cells (HRCs) and Na+ pump-rich cells (NaRCs) and slightly expressed in Na+/Cl- cotrasporter (NCC) cells and keratinocytes of larval skin. Using morpholino knockdown technique to suppress the protein expression of aqp1a and scanning ion-selective electrode technique (SIET) to analyze carbonic acid formation at the surface of specific skin cells, this study demonstrates that aqp1a plays a critical role in CO2 diffusion across the skin of zebrafish larvae. 生命科學系